Profitability as a Mediator of the Effects of Green Accounting, CSR, and Environmental Performance on Firm Value in Indonesia’s Raw Materials Sector - Shafri Zakariyya Rasyid; Suyatmin Waskito Adi (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study examines the effects of Green Accounting, Corporate Social Responsibility (CSR), and Environmental Performance on firm value, with profitability as a mediating variable, in basic materials companies listed on the Indonesia Stock Exchange during 2021–2023. Research Method: This study uses a quantitative approach with secondary data from annual reports, sustainability reports, and PROPER ratings. The sample includes 57 observations selected through purposive sampling. Data were analyzed using multiple linear regression, path analysis, and the Sobel test with SPSS. Results and Discussion: The findings show that Green Accounting has a negative and significant effect on profitability but a positive effect on firm value. Environmental Performance positively and significantly affects profitability, while CSR has no significant effect on profitability or firm value. Profitability significantly affects firm value but does not mediate the relationships among Green Accounting, CSR, Environmental Performance, and firm value. Implications: The findings encourage companies to strengthen environmental management and transparent sustainability disclosure to improve firm value and investor confidence. Originality: This study simultaneously examines Green Accounting, CSR, Environmental Performance, and profitability in Indonesian basic materials companies.